Proposing an International Standard Accident Number for Interconnecting Information and Communication Technology Systems of the Rescue Chain - Spicher, Nicolai; Barakat, Ramon; Wang, Ju; Haghi, Mostafa; Jagieniak, Justin; Öktem, Gamze Söylev; Hackel, Siegfried; Deserno, Thomas Martin (Methods of Information in Medicine, 2021)
Background The rapid dissemination of smart devices within the internet of things (IoT) is developing toward automatic emergency alerts which are transmitted from machine to machine without human interaction. However, apart from individual projects concentrating on single types of accidents, there is no general methodology of connecting the standalone information and communication technology (ICT) systems involved in an accident: systems for alerting (e.g., smart home/car/wearable), systems in the responding stage (e.g., ambulance), and in the curing stage (e.g., hospital).Objectives We define the International Standard Accident Number (ISAN) as a unique token for interconnecting these ICT systems and to provide embedded data describing the circumstances of an accident (time, position, and identifier of the alerting system).Materials and Methods Based on the characteristics of processes and ICT systems in emergency care, we derive technological, syntactic, and semantic requirements for the ISAN, and we analyze existing standards to be incorporated in the ISAN specification.Results We choose a set of formats for describing the embedded data and give rules for their combination to generate an ISAN. It is a compact alphanumeric representation that is generated easily by the alerting system. We demonstrate generation, conversion, analysis, and visualization via representational state transfer (REST) services. Although ISAN targets machine-to-machine communication, we give examples of graphical user interfaces.Conclusion Created either locally by the alerting IoT system or remotely using our RESTful service, the ISAN is a simple and flexible token that enables technological, syntactic, and semantic interoperability between all ICT systems in emergency care.
Keywords: accidents (D000059); emergency medical services (D004632); emergency medical service communication systems (D004631); health information interoperability (D000073892); internet of things (D00008s0487)